2015
DOI: 10.3390/rel6041249
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Spirituality, Health-Related Quality of Life, and Depression in Pre-Dialysis Chronic Kidney Disease Patients: An Exploratory Analysis in Thai Buddhist Patients

Abstract: Abstract:There are numerous studies of quality of life (QOL) in chronic kidney disease (CKD) patients; however, there are a few studies of spirituality and its association with QOL. Previous studies were done focusing on Western cultures; thus, the study of CKD patients in Eastern cultures would reveal interesting insights. This study was conducted to explore the spirituality, QOL, and depression of Thai CKD patients, and the associations between spirituality, QOL, and depression. This cross-sectional descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The standardised T-scores of PHS and MHS are stratified by gender and age-group and based on the average values for the generally healthy Thai population. The 9-THAI is composed of 7 domains and 2 global health ratings, and encourages subjects to rate their experiences with health conditions during the past month (Saisunantararom et al, 2015). Response choices for the 7 domains are interpreted according to the perceived severity of the problems on a 5point scale, where 1 = "very severe", 2 = "severe", 3 = "moderate", 4 = "mild", and 5 = "not at all".…”
Section: Instrumentsmentioning
confidence: 99%
“…The standardised T-scores of PHS and MHS are stratified by gender and age-group and based on the average values for the generally healthy Thai population. The 9-THAI is composed of 7 domains and 2 global health ratings, and encourages subjects to rate their experiences with health conditions during the past month (Saisunantararom et al, 2015). Response choices for the 7 domains are interpreted according to the perceived severity of the problems on a 5point scale, where 1 = "very severe", 2 = "severe", 3 = "moderate", 4 = "mild", and 5 = "not at all".…”
Section: Instrumentsmentioning
confidence: 99%
“…Several systematic reviews of the literature support a relationship between religiosity promoting improved health behaviors (Oji et al 2017;Saad and Medeiros 2017) and lower all-cause mortality (Hatah et al 2015;McCullough et al 2000;Powell et al 2003;Saad and Medeiros 2017). Emerging evidence suggests that R/S are correlated with improved mental and physical health outcomes, including decreased rates of depression (Bonelli et al 2012;El-Hady and Kandeel 2017;Frih et al 2017;Kazemi and Baharami 2014;Saisunantararom et al 2015), anxiety, post-traumatic stress disorder, suicide, and coronary heart disease (Bashar et al 2018). Additionally, research in Muslim populations suggests that religious practice may generate physiologic changes that are clinically evident.…”
Section: Religiosity and Spiritualitymentioning
confidence: 99%
“…Research has consistently linked indices of religious coping to measures of health and well-being, a major source of support and hope, among diverse groups recovering from physical and mental illness or facing critical life events (Alves et al 2010;Marcantonio et al 2005;Mardiyono et al 2011;Saisunantararom et al 2015;Shehabi et al 2010). Hence, these are factors of vital importance to many ICU and their families (Shinall et al 2014;Wall et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies have demonstrated that there is an inverse relationship between spirituality and depression, even in different cultures (Bekelman et al 2007;Saisunantararom et al 2015). Bornet et al (Bornet et al 2015) have tested two instruments for measuring depressive symptoms and spiritual distress, namely the Geriatric Depression Scale (GDS) and the Spiritual Distress Assessment Tool (SDAT).…”
Section: Depression and Spiritual Distressmentioning
confidence: 99%